In vitro and in silico studies of the membrane permeability of natural flavonoids from Silybum marianum (L.) Gaertn. and their derivatives - Diukendjieva, Antonia; Alov, Petko; Tsakovska, Ivanka; Pencheva, Tania; Richarz, Andrea; Kren, Vladimir; Cronin, Mark T D; Pajeva, Ilza (Phytomedicine, 2019)
BACKGROUND: In recent years the number of natural products used as pharmaceuticals, components of dietary supplements and cosmetics has increased tremendously requiring more extensive evaluation of their pharmacokinetic properties. PURPOSE: This study aims at combining in vitro and in silico methods to evaluate the gastrointestinal absorption (GIA) of natural flavonolignans from milk thistle (Silybum marianum (L.) Gaertn.) and their derivatives. METHODS: A parallel artificial membrane permeability assay (PAMPA) was used to evaluate the transcellular permeability of the plant main components. A dataset of 269 compounds with measured PAMPA values and specialized software tools for calculating molecular descriptors were utilized to develop a quantitative structure-activity relationship (QSAR) model to predict PAMPA permeability. RESULTS: The PAMPA permeabilities of 7 compounds constituting the main components of the milk thistle were measured and their GIA was evaluated. A freely-available and easy to use QSAR model predicting PAMPA permeability from calculated physico-chemical molecular descriptors was derived and validated on an external dataset of 783 compounds with known GIA. The predicted permeability values correlated well with obtained in vitro results. The QSAR model was further applied to predict the GIA of 31 experimentally untested flavonolignans. CONCLUSIONS: According to both in vitro and in silico results most flavonolignans are highly permeable in the gastrointestinal tract, which is a prerequisite for sufficient bioavailability and use as lead structures in drug development. The combined in vitro/in silico approach can be used for the preliminary evaluation of GIA and to guide further laboratory experiments on pharmacokinetic characterization of bioactive compounds, including natural products.
Keywords: flavonoidy; Flavonoids; ostropestřec mariánský; Humans; membrány umělé; Computer Simulation; permeabilita buněčné membrány; Silybum marianum; lidé; Flavonolignans; Quantitative Structure-Activity Relationship; počítačová simulace; Cell Membrane Permeability; Membranes, Artificial; potravní doplňky; Dietary Supplements; kvantitativní vztahy mezi strukturou a aktivitou; intestinální absorpce; flavonolignany; Intestinal Absorption